Predation on Elachistocleis bicolor (Anura: Microhylidae) by Lethocerus annulipes (Heteroptera: Belostomatidae) - Zaracho, Victor Hugo (2012)
The purpose of this note is to report an adult giant water bug (Belostomatidae) feeding on two adult microhylid frogs Elachistocleis bicolor.